Youth Lifestyle in A Moslem Magazine: A Reception Analysis on “Muslimah” Readers - Nisa, Airin; Reciana, Ken; Atmonobudi, Billy K. Sarwono (Mediator, 2007)
This research is about whether or not Indonesian female youth Moslem are easily accepting religious values packaged with popular icons in a Moslem magazine. In this magazine, teenagers do not have to wear long, loose dark colored clothes, but they may wear light colored, tight and trendy dresses known as modern hijab. The main goal of this research is understanding female youths’ reception over Muslimah magazine applying Stuart Hall’s encoding and decoding approach. Primary data were collected by in-depth interview toward selected readers. The results are: (1) the ability of parents to control their teenagers’ religious behavior affect teenagers’ reading over Muslimah. (2) Informants who live with their parents younger than 20 years old, and have strong connection with religious peer group—tend to build negotiated readings. (3) Informants who do not depend on their parents—older than 20 years old, and have professional jobs—tend to rely more on mass media for seeking religious information more than their peer group or parents. Therefore, they tend to agree with Muslimah coverage which emphasized more on modern Moslem youth lifestyle than on its syariah (religious values).